Ant colony optimization for the topological design of interior permanent magnet (IPM) machines. Issue 3 (29th April 2014) - S. Batista, Lucas; Campelo, Felipe; G. Guimarães, Frederico; A. Ramírez, Jaime; Li, Min; A. Lowther, David
Abstract : Purpose: – The purpose of this paper is to apply an Ant colony optimization approach for the solution of the topological design of interior permanent magnet (IPM) machines. Design/methodology/approach: – The IPM motor design domain is discretized into a suitable equivalent graph representation and an Ant System (AS) algorithm is employed to achieve an efficient distribution of materials into this graph. Findings: – The single-objective problems associated with the maximization of the torque and with the maximization of the shape smoothness of the IPM are investigated. The rotor of the device is discretized into a 9×18 grid in both cases, and three different materials are considered: air, iron and permanent magnet. Research limitations/implications: – The graph representation used enables the solution of topological design problems with an arbitrary number of materials, which is relevant for 2 and 3D problems. Originality/value: – From the numerical experiments, the AS algorithm was able to achieve reasonable shapes and torque values for both design problems. The results show the relevance of the mechanism for multi-domain topology optimization of electromagnetic devices.